A Single Mutation Increases the Activity and Stability of Pectobacterium carotovorum Nitrile Reductase. (19th January 2018) - Zhou, Zheng; Li, Min; Xu, Jian‐He; Zhang, Zhi‐Jun
Abstract: Nitrile reductases are considered to be promising and environmentally benign nitrile‐reducing biocatalysts to replace traditional metal catalysts. Unfortunately, the catalytic efficiencies of the nitrile reductases reported so far are very low. To date, all attempts to increase the catalytic activity of nitrile reductases by protein engineering have failed. In this work, we successfully increased the specific activity of a nitrile reductase from Pectobacterium carotovorum from 354 to 526 U gprot −1 by engineering the substrate binding pocket; moreover, the thermostability was also improved (≈2‐fold), showing half‐lives of 140 and 32 h at 30 and 40 °C, respectively. In the bioreduction of 2‐amino‐5‐cyanopyrrolo[2, 3‐ d ]pyrimidin‐4‐one (preQ0 ) to 2‐amino‐5‐aminomethylpyrrolo[2, 3‐ d ]pyrimidin‐4‐one (preQ1 ), the variant was advantageous over the wild‐type enzyme with a higher reaction rate and complete conversion of the substrate within a shorter period. Homology modeling and docking analysis revealed some possible origins of the increased activity and stability. These results establish a solid basis for future engineering of nitrile reductases to increase the catalytic efficiency further, which is a prerequisite for applying these novel biocatalysts in synthetic chemistry. Abstract : Reduced to clear : The nitrile reductase from Pectobacterium carotovorum is able to catalyze the reduction of nitriles to primary amines with the consumption of two molecules of NADPH. A single mutation at the entrance of the substrate channel increases both the activity and stability of the nitrile reductase.